Development of tubular coated electrodes for underwater wet welding. - Queiroz Bracarense, Alexandre; Perdomo González, Lorenzo; Pereira Pessoa, Ezequiel Caires; Quintana Puchol, Rafael (Revista Técnica da Faculdade de Engenharia da de Zulia, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The structural configuration of the tubular coated electrodes offers an attractive field of metallurgical and technological investigation on the underwater wet welding. For this reason, in this work the developed experiments with tubular coated electrodes using as base the covering of the rutile electrode (6013) are presented. Three different powder mixtures were formulated and filled the tubular wires cavities. Finally two electrodes were selected and the waterproof varnish with pirometallugical mixtures was modified. The deposits were made in an aquarium with a water layer of 1m. The obtained results revealed that the mixture formed by manganese oxide and aluminum as inside the electrode as in the waterproof varnish offered the best results in the technological and metallurgical behaviors of the underwater wet welding, showing that the tubular coated electrodes constitute a viable alternative for the development of consumable for the wet welding process.